THE EFFECT OF REGIONAL FINANCIAL PERFORMANCE ON QUALITY OF LIFE OF PEOPLE IN EAST JAVA IN 2020-2022 - Liana; Faisol, Amin Tohari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This study aims to analyze the financial performance of local governments in East Java and its impact on the quality of life of communities, measured by effectiveness, efficiency, and autonomy, from 2020 to 2022. The research uses a saturated sampling technique, analyzing data from all regencies/cities in East Java Province. Data is analyzed using panel data regression with the Random Effect Model method. The results show that financial performance, measured through efficiency, effectiveness, and autonomy, has a significant impact on per capita income, a proxy for quality of life. Partial test results indicate that the effectiveness and efficiency of financial performance have a significant impact on the quality of life of communities, while financial autonomy does not have a significant impact on the quality of life.